2021
DOI: 10.36941/jesr-2021-0069
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Literature (YAL): An Analytical Study Among Selected EFL Teachers in Jordanian Public Schools

Abstract: The purpose of this study is to shed light on Young Adult literature (YAL) in Jordan. Eleven English as a foreign language (EFL) teachers and 62 EFL students in Jordanian public schools participated in this research to first measure their awareness of the YAL and to evaluate the academic benefits of integrating English YA literature into the Jordanian public school curricula. A group of EFL instructors and EFL learners were interviewed using a semi-structured guide. The instructors' interview questions focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This implied that young adult literature has effect on the morals of senior secondary school students. The result was in tandem with (Yassin & Saed, 2021) in a study titled young adult literature, an analytical study among selected eleven English as a foreign language found that young adult literature positively affects morals, motivation and engagement. According to the findings of (Salam, 2015), young adult literature reinforces beliefs and values while also encouraging moral development.…”
Section: Discussionsupporting
confidence: 54%
“…This implied that young adult literature has effect on the morals of senior secondary school students. The result was in tandem with (Yassin & Saed, 2021) in a study titled young adult literature, an analytical study among selected eleven English as a foreign language found that young adult literature positively affects morals, motivation and engagement. According to the findings of (Salam, 2015), young adult literature reinforces beliefs and values while also encouraging moral development.…”
Section: Discussionsupporting
confidence: 54%
“…Students noticed that while using YAL, their reading capacity and skills had increased (Irion, 2018). Based on Yassin & Saed (2021), EFL students who had the opportunity to read some English YA narratives during the course were able to explore the uniqueness of the human condition regardless of ability, heritage, discourse, or faith; they were also able to develop strong bonds with YAL and the personalities inside them while also enhancing their English proficiency. As students read literary works, they become more aware of the language employed.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Extensive reading of YA fiction is one of the effective procedures for growing their English linguistics professions (Yassin & Saed, 2021). It meant that students could improve their reading skill especially narrative text by reading YAL extensively.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations